Behaviour of lightweight foamed concrete with pre-tensioning steel straps confinement - Faisal, Amsyar; Ma, Chau Khun; Wahid, Omar; Abdullah Zawawi, Awang; Shek, Poi Ngian (IOP Publishing, 2019)
Due to its low compressive strength and ductility, lightweight foamed concrete (LFC) cannot be used in structural members such as beams, slabs and columns. One way to improve the strength and ductility of LFC is by confining the concrete laterally by using active external confinement. This research therefore aimed to investigate the effectiveness of external confinement by using low cost steel straps tensioning technique (SSTT) to the LFC columns. A total of 36 cylindrical specimens with 100 mm diameter, 200 mm height and density of 1500 kg/m3, 1650 kg/m3 and 1800 kg/m3 were prepared in this study. The strength of the LFC columns was significantly improved with the increase in number of layers and decrease in spacing of the SSTT confinement. This paper also presents the axial compression stress-strain relationship of the SSTT-confined LFC. SSTT confinement is proven to be effective in increasing the performance of the LFC columns, especially in the specimens with the density of 1500 kg/m3.